A low surface voltage silicone rubber composition and a method for preparing the same
Patent Information
- Application Number
- CN202611112833.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-25
- Publication Date
- 2026-10-23
AI Technical Summary
甲基乙烯基封端的硅氧烷100份;
1、由于本申请通过在硅橡胶中加入N-丙基-N-甲基吡咯烷双(三氟甲烷磺酰)亚胺盐、三丁基甲基铵双(三氟甲烷磺酰)亚胺盐复配而成的离子液体与酯化木质素、烷基化木质素复配而成的木质素,在特殊的离子液体与特殊的木质素的配合下,离子液体添加量仅为0.1-0.3份的情况下依然能显著降低硅橡胶的表面电压,由于离子液体添加量较低,从而使得对硅橡胶电阻性能的影响较少,使得硅橡胶能保持较高的表面电阻和体积电阻,制得的硅橡胶具有较好的绝缘性能同时表面不易积累静电,不易出现高静电压破坏电子元器件的情况,很好的满足高绝缘且对静电压敏感的应用场景所需。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of silicone rubber materials, and in particular to a silicone rubber composition with low surface voltage and a method for preparing the same. Background Technology
[0002] Silicone rubber, as an excellent insulating material, is widely used in various electronic fields. However, while ordinary silicone rubber provides good insulation, its surface is prone to accumulating static electricity after friction. When the static voltage is too high, it can easily damage electronic components such as chips. Therefore, when silicone rubber is used in precision electronic components, it is necessary to reduce the surface static voltage of the silicone rubber. The existing technology mainly reduces the surface voltage of silicone rubber by adding ionic liquids. However, to achieve the effect of reducing the surface voltage, 3-7 parts of ionic liquid need to be added. Such a high amount of ionic liquid will significantly reduce the resistance of silicone rubber, resulting in a significant decrease in the insulation performance of silicone rubber. It is difficult to meet the application scenarios that require high insulation and are sensitive to static voltage. Therefore, there is still room for improvement. Summary of the Invention
[0003] In order to enable silicone rubber to have high surface resistance and volume resistance while having low surface voltage, this application provides a silicone rubber composition with low surface voltage and a method for preparing the same.
[0004] In a first aspect, this application provides a silicone rubber composition with low surface voltage, employing the following technical solution: A low surface voltage silicone rubber composition comprising the following components in parts by weight: 100 parts of methyl vinyl-terminated siloxane; 40-60 parts of silica; 0.5-0.7 parts of silane coupling agent; 4.5-5.5 parts of structure control agent; Internal release agent 0.3-0.6 parts; 0.1-0.3 parts of ionic liquid; 2-4 parts lignin; The ionic liquid is a combination of N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt and tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt; The lignin is a blend of esterified lignin and alkylated lignin.
[0005] By adopting the above technical solution, an ionic liquid composed of N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt and tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt is added to silicone rubber, along with lignin composed of esterified lignin and alkylated lignin. Under the combination of special ionic liquid and special lignin, the surface voltage of silicone rubber can still be significantly reduced even when the amount of ionic liquid added is only 0.1-0.3 parts. Due to the low amount of ionic liquid added, the impact on the resistivity of silicone rubber is minimal, allowing the silicone rubber to maintain high surface resistance and volume resistivity. The resulting silicone rubber has good insulation properties and is not prone to static electricity accumulation on the surface, making it less likely to cause high static voltage to damage electronic components. It well meets the requirements of high insulation and static voltage sensitive application scenarios.
[0006] Preferably, in the ionic liquid, the mass ratio of N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt to tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt is 0.05-0.15:0.05-0.15.
[0007] By adopting the above technical solution and specifically selecting the mass ratio of N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt and tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt, the effect of combining with lignin is better, and the surface voltage can be reduced more effectively.
[0008] Preferably, the mass ratio of esterified lignin to alkylated lignin in the lignin is 1-2:1-2.
[0009] By adopting the above technical solution and specifically selecting the mass ratio of esterified lignin and alkylated lignin, the effect of combining with ionic liquid is better, and the effect of reducing surface voltage is more effective.
[0010] Preferably, the structure control agent is a compound of hydroxyl silicone oil and diethoxydimethylsilane.
[0011] By adopting the above technical solution and specifically selecting hydroxyl silicone oil and diethoxydimethylsilane, the processing difficulty and the storage time of the rubber compound are reduced, which is more effective.
[0012] Preferably, in the structure control agent, the mass ratio of hydroxyl silicone oil to diethoxydimethylsilane is 1.5-2.5:2.5-3.
[0013] By adopting the above technical solution and specifically selecting the mass ratio of hydroxyl silicone oil and diethoxydimethylsilane, the effect of improving processing performance is even better.
[0014] Preferably, the internal release agent is zinc stearate.
[0015] By adopting the above technical solution and specifically selecting zinc stearate, the demolding effect is better.
[0016] Preferably, the silane coupling agent is a combination of vinyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.
[0017] By adopting the above technical solutions and specifically selecting vinyltrimethoxysilane and γ-methacryloyloxypropyltrimethoxysilane, the reinforcing effect of silica on silicone rubber can be better improved.
[0018] Preferably, in the silane coupling agent, the mass ratio of vinyltrimethoxysilane to γ-methacryloxypropyltrimethoxysilane is 0.2-0.3:0.3-0.4.
[0019] By adopting the above technical solution and by specifically selecting the mass ratio of vinyltrimethoxysilane and γ-methacryloyloxypropyltrimethoxysilane, the effect of silica reinforcing silicone rubber is better.
[0020] Secondly, this application provides a method for preparing a silicone rubber composition with low surface voltage, using the following technical solution: A method for preparing the above-mentioned low surface voltage silicone rubber composition includes the following steps: Step 1), mix the methyl vinyl-terminated siloxane, silane coupling agent, structure control agent, internal release agent and ionic liquid evenly to obtain a premixed adhesive; Step 2), add the silica to the premixed adhesive in 4-6 portions, and add all the lignin when adding the silica for the first time. Knead and stir evenly to obtain the mixed adhesive. Step 3), at 140-145℃, reduce the pressure to 0.05-0.08MPa, and continue kneading and stirring for 60-70 minutes to obtain the pretreated adhesive; Step 4): After cooling the pretreated adhesive to room temperature, grind the pretreated adhesive to obtain a silicone rubber composition with low surface voltage.
[0021] By adopting the above technical solution and grinding, lignin is evenly dispersed in silicone rubber, and the resulting silicone rubber has high resistance and low surface voltage.
[0022] In summary, this application has the following beneficial effects: 1. This application utilizes an ionic liquid, formulated by combining N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt and tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt, with lignin, formulated by combining esterified lignin and alkylated lignin. With the special combination of ionic liquid and lignin, even with an ionic liquid addition of only 0.1-0.3 parts, the surface voltage of the silicone rubber can still be significantly reduced. Due to the low amount of ionic liquid added, the impact on the resistivity of the silicone rubber is minimal, allowing the silicone rubber to maintain high surface and volume resistivity. The resulting silicone rubber exhibits good insulation properties and is less prone to static electricity accumulation on its surface, thus reducing the likelihood of high static voltage damaging electronic components. This effectively meets the requirements of applications requiring high insulation and sensitive to static voltage.
[0023] 2. In this application, the preferred method is to specifically select the mass ratio of N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt, and the mass ratio of esterified lignin and alkylated lignin, so that the ionic liquid and lignin can work together better and reduce the surface voltage more effectively.
[0024] 3. The method of this application, through grinding, makes the lignin uniformly dispersed in the silicone rubber, and the resulting silicone rubber has high resistance and low surface voltage. Detailed Implementation
[0025] The present application will be further described in detail below with reference to the embodiments. Example
[0026] A low surface voltage silicone rubber composition, prepared by the following steps: Step 1): 100 kg of methyl vinyl-terminated siloxane, 0.2 kg of vinyltrimethoxysilane, 0.3 kg of γ-methacryloyloxypropyltrimethoxysilane, 2 kg of hydroxyl silicone oil, 2.5 kg of diethoxydimethylsilane, 0.3 kg of zinc stearate, 0.05 kg of N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, and 0.05 kg of tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt are added to a kneader and kneaded at 60 r / min for 15 min to obtain a premixed rubber.
[0027] Step 2): Add 40 kg of silica to the premixed rubber in four equal portions. When adding silica for the first time, add 1 kg of esterified lignin and 1 kg of alkylated lignin. After all silica is added, mix at 60 r / min for 15 min to obtain the mixed rubber.
[0028] Step 3), adjust the rotation speed to raise the temperature of the mixed rubber to 140℃, reduce the pressure to 0.05MPa, control the temperature of the mixed rubber at 140℃, and mix for 60 minutes to obtain the pretreated rubber.
[0029] Step 4): Discharge the pretreated adhesive, cool it to room temperature, and then put the pretreated adhesive into a three-roll mill and grind it repeatedly three times to obtain a silicone rubber composition with low surface voltage.
[0030] The methyl vinyl-terminated siloxane was purchased from Hoshine Silicon Industry Co., Ltd., model 110 series, with a vinyl content of 0.23%.
[0031] Vinyltrimethoxysilane was purchased from Hubei Xinlantian New Materials Co., Ltd., model A171.
[0032] γ-Methacryloxypropyltrimethoxysilane was purchased from Hubei Xinlantian New Materials Co., Ltd., model KH-570. The hydroxyl silicone oil was purchased from Zhejiang Zhenghe Silicon Materials, model 207-30.
[0033] Diethoxydimethylsilane was purchased from Hangzhou Jessica Chemical Co., Ltd., model KH-2122.
[0034] Zinc stearate was purchased from San Yi Chemical in Singapore, SAK-ZS-PLB.
[0035] N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt was purchased from Maclean's, CAS No.: 223437-05-6.
[0036] Tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt was purchased from Maclean's, CAS No.: 405514-94-5.
[0037] The silica was purchased from Hubei Huifu Nanomaterials Co., Ltd., model HL-200.
[0038] Esterified lignin was purchased from Jinan Shengquan Group Co., Ltd., model SQWS-2.
[0039] The alkylated lignin was purchased from Jinan Shengquan Group Co., Ltd., model SQTF-1. Example
[0040] A low surface voltage silicone rubber composition, prepared by the following steps: Step 1): 100 kg of methyl vinyl-terminated siloxane, 0.25 kg of vinyltrimethoxysilane, 0.35 kg of γ-methacryloyloxypropyltrimethoxysilane, 1.5 kg of hydroxyl silicone oil, 3 kg of diethoxydimethylsilane, 0.45 kg of zinc stearate, 0.1 kg of N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, and 0.1 kg of tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt are added to a kneader and kneaded at 60 r / min for 15 min to obtain a premixed rubber.
[0041] Step 2): Add 50 kg of silica to the premixed rubber in 5 equal portions. When adding silica for the first time, add 1.5 kg of esterified lignin and 1.5 kg of alkylated lignin. After all silica is added, mix at 60 r / min for 15 min to obtain the mixed rubber.
[0042] Step 3), adjust the rotation speed to raise the temperature of the mixed rubber to 142℃, reduce the pressure to 0.06MPa, control the temperature of the mixed rubber at a constant 142℃, and mix for 65 minutes to obtain the pretreated rubber.
[0043] Step 4): Discharge the pretreated adhesive, cool it to room temperature, and then put the pretreated adhesive into a three-roll mill and grind it repeatedly three times to obtain a silicone rubber composition with low surface voltage.
[0044] The methyl vinyl-terminated siloxane was purchased from Hoshine Silicon Industry Co., Ltd., model 110 series, with a vinyl content of 0.23%.
[0045] Vinyltrimethoxysilane was purchased from Hubei Xinlantian New Materials Co., Ltd., model A171.
[0046] γ-Methacryloxypropyltrimethoxysilane was purchased from Hubei Xinlantian New Materials Co., Ltd., model KH-570. The hydroxyl silicone oil was purchased from Zhejiang Zhenghe Silicon Materials, model 207-30.
[0047] Diethoxydimethylsilane was purchased from Hangzhou Jessica Chemical Co., Ltd., model KH-2122.
[0048] Zinc stearate was purchased from San Yi Chemical in Singapore, SAK-ZS-PLB.
[0049] N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt was purchased from Maclean's, CAS No.: 223437-05-6.
[0050] Tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt was purchased from Maclean's, CAS No.: 405514-94-5.
[0051] The silica was purchased from Hubei Huifu Nanomaterials Co., Ltd., model HL-200.
[0052] Esterified lignin was purchased from Jinan Shengquan Group Co., Ltd., model SQWS-2.
[0053] The alkylated lignin was purchased from Jinan Shengquan Group Co., Ltd., model SQTF-1. Example
[0054] A low surface voltage silicone rubber composition, prepared by the following steps: Step 1): 100 kg of methyl vinyl-terminated siloxane, 0.3 kg of vinyltrimethoxysilane, 0.4 kg of γ-methacryloyloxypropyltrimethoxysilane, 2.5 kg of hydroxyl silicone oil, 3 kg of diethoxydimethylsilane, 0.6 kg of zinc stearate, 0.15 kg of N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, and 0.15 kg of tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt are added to a kneader and kneaded at 60 r / min for 15 min to obtain a premixed rubber.
[0055] Step 2): Add 60 kg of silica to the premixed rubber in 6 equal portions. When adding silica for the first time, add 2 kg of esterified lignin and 2 kg of alkylated lignin. After all silica is added, mix at 60 r / min for 15 min to obtain the mixed rubber.
[0056] Step 3), adjust the rotation speed to raise the temperature of the mixed rubber to 145℃, reduce the pressure to 0.08MPa, control the temperature of the mixed rubber at 145℃, and mix for 70 minutes to obtain the pretreated rubber.
[0057] Step 4): Discharge the pretreated adhesive, cool it to room temperature, and then put the pretreated adhesive into a three-roll mill and grind it repeatedly three times to obtain a silicone rubber composition with low surface voltage.
[0058] The methyl vinyl-terminated siloxane was purchased from Hoshine Silicon Industry Co., Ltd., model 110 series, with a vinyl content of 0.23%.
[0059] Vinyltrimethoxysilane was purchased from Hubei Xinlantian New Materials Co., Ltd., model A171.
[0060] γ-Methacryloxypropyltrimethoxysilane was purchased from Hubei Xinlantian New Materials Co., Ltd., model KH-570. The hydroxyl silicone oil was purchased from Zhejiang Zhenghe Silicon Materials, model 207-30.
[0061] Diethoxydimethylsilane was purchased from Hangzhou Jessica Chemical Co., Ltd., model KH-2122.
[0062] Zinc stearate was purchased from San Yi Chemical in Singapore, SAK-ZS-PLB.
[0063] N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt was purchased from Maclean's, CAS No.: 223437-05-6.
[0064] Tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt was purchased from Maclean's, CAS No.: 405514-94-5.
[0065] The silica was purchased from Hubei Huifu Nanomaterials Co., Ltd., model HL-200.
[0066] Esterified lignin was purchased from Jinan Shengquan Group Co., Ltd., model SQWS-2.
[0067] The alkylated lignin was purchased from Jinan Shengquan Group Co., Ltd., model SQTF-1.
[0068] Comparative Example 1 A low surface voltage silicone rubber composition, differing from Example 2 only in that: The following methods were employed: replacing N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt with an equal amount of 1-vinyl-3-ethylimidazolium hexafluorophosphate; replacing tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt with an equal amount of 1-ethyl-3-methylimidazolium dinitrile amine salt; replacing esterified lignin with an equal amount of lignin sulfonate; and replacing alkylated lignin with enzymatically hydrolyzed lignin.
[0069] 1-Vinyl-3-ethylimidazolium hexafluorophosphate was purchased from Wuhan Smike Biotechnology Co., Ltd.
[0070] 1-Ethyl-3-methylimidazolium dinitrile amine salt was purchased from Hubei Hongxin Ruiyu Fine Chemical Co., Ltd.
[0071] The lignin sulfonate was purchased from Jinan Shengquan Group Co., Ltd., model SQDL-1.
[0072] The enzymatically hydrolyzed lignin was purchased from Wuhan Jiyesheng Chemical Co., Ltd., model A01095.
[0073] Comparative Example 2 A low surface voltage silicone rubber composition, differing from Example 2 only in that: The N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt was replaced with an equal amount of 1-vinyl-3-ethylimidazolium hexafluorophosphate.
[0074] 1-Vinyl-3-ethylimidazolium hexafluorophosphate was purchased from Wuhan Smike Biotechnology Co., Ltd.
[0075] Comparative Example 3 A low surface voltage silicone rubber composition, differing from Example 2 only in that: The tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt was replaced with an equal amount of 1-ethyl-3-methylimidazolium dinitrile ammonium salt.
[0076] 1-Ethyl-3-methylimidazolium dinitrile amine salt was purchased from Hubei Hongxin Ruiyu Fine Chemical Co., Ltd.
[0077] Comparative Example 4 A low surface voltage silicone rubber composition, differing from Example 2 only in that: The N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt was replaced by an equal amount of 1-vinyl-3-ethylimidazolium hexafluorophosphate, and the tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt was replaced by an equal amount of 1-ethyl-3-methylimidazolium dinitrileamine salt.
[0078] 1-Vinyl-3-ethylimidazolium hexafluorophosphate was purchased from Wuhan Smike Biotechnology Co., Ltd.
[0079] 1-Ethyl-3-methylimidazolium dinitrile amine salt was purchased from Hubei Hongxin Ruiyu Fine Chemical Co., Ltd.
[0080] Comparative Example 5 A low surface voltage silicone rubber composition, differing from Example 2 only in that: Esterified lignin was replaced with an equal amount of lignin sulfonate.
[0081] The lignin sulfonate was purchased from Jinan Shengquan Group Co., Ltd., model SQDL-1.
[0082] Comparative Example 6 A low surface voltage silicone rubber composition, differing from Example 2 only in that: Enzymatically hydrolyzed lignin was used to replace alkylated lignin in equal amounts.
[0083] The enzymatically hydrolyzed lignin was purchased from Wuhan Jiyesheng Chemical Co., Ltd., model A01095.
[0084] Comparative Example 7 A low surface voltage silicone rubber composition, differing from Example 2 only in that: Esterified lignin was replaced by lignin sulfonate in equal amounts, and alkylated lignin was replaced by enzymatically hydrolyzed lignin in equal amounts.
[0085] The lignin sulfonate was purchased from Jinan Shengquan Group Co., Ltd., model SQDL-1.
[0086] The enzymatically hydrolyzed lignin was purchased from Wuhan Jiyesheng Chemical Co., Ltd., model A01095.
[0087] Comparative Example 8 A low surface voltage silicone rubber composition, differing from Example 2 only in that: The N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt was replaced by an equal amount of 1-vinyl-3-ethylimidazolium hexafluorophosphate, and the tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt was replaced by an equal amount of 1-vinyl-3-ethylimidazolium hexafluorophosphate.
[0088] 1-Vinyl-3-ethylimidazolium hexafluorophosphate was purchased from Wuhan Smike Biotechnology Co., Ltd.
[0089] Comparative Example 9 A low surface voltage silicone rubber composition, differing from Example 2 only in that: The N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt was replaced by an equal amount of 1-ethyl-3-methylimidazolium dinitrile amide salt, and the tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt was replaced by an equal amount of 1-ethyl-3-methylimidazolium dinitrile amide salt.
[0090] 1-Ethyl-3-methylimidazolium dinitrile amine salt was purchased from Hubei Hongxin Ruiyu Fine Chemical Co., Ltd.
[0091] Comparative Example 10 A low surface voltage silicone rubber composition, differing from Example 2 only in that: The tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt was replaced with an equal amount of N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt.
[0092] Comparative Example 11 A low surface voltage silicone rubber composition, differing from Example 2 only in that: The N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt was replaced with an equal amount of tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt.
[0093] Comparative Example 12 A low surface voltage silicone rubber composition, differing from Example 2 only in that: Esterified lignin was replaced by lignin sulfonate in equal amounts, and alkylated lignin was replaced by lignin sulfonate in equal amounts.
[0094] The lignin sulfonate was purchased from Jinan Shengquan Group Co., Ltd., model SQDL-1.
[0095] Comparative Example 13 A low surface voltage silicone rubber composition, differing from Example 2 only in that: Enzymatically hydrolyzed lignin was used to replace esterified lignin in equal amounts, and enzymatically hydrolyzed lignin was used to replace alkylated lignin in equal amounts.
[0096] The enzymatically hydrolyzed lignin was purchased from Wuhan Jiyesheng Chemical Co., Ltd., model A01095.
[0097] Comparative Example 14 A low surface voltage silicone rubber composition, differing from Example 2 only in that: Esterified lignin was used to replace alkylated lignin in equal amounts.
[0098] Comparative Example 15 A low surface voltage silicone rubber composition, differing from Example 2 only in that: Alkylated lignin was used to replace esterified lignin in equal amounts.
[0099] Comparative Example 16 A low surface voltage silicone rubber composition, differing from Example 2 only in that: Equal amounts of silica were used to replace N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, equal amounts of silica were used to replace tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt, equal amounts of silica were used to replace esterified lignin, and equal amounts of silica were used to replace alkylated lignin.
[0100] Comparative Example 17 A low surface voltage silicone rubber composition, differing from Example 2 only in that: Esterified lignin was replaced with an equal amount of silica, and alkylated lignin was replaced with an equal amount of silica.
[0101] Comparative Example 18 A low surface voltage silicone rubber composition, differing from Example 2 only in that: Equal amounts of silica were used to replace N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, and equal amounts of silica were used to replace tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt.
[0102] Experiment 1 The low surface voltage silicone rubber compositions of each embodiment and comparative example were mixed with a vulcanizing agent and vulcanized to obtain the test samples.
[0103] Preparation of the test sample: Take 98.5g of a low surface voltage silicone rubber composition and 1.5g of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane and put them into a two-roll mill. Mill for 5 minutes, then pass through a thin mill 30 times to obtain the compound.
[0104] The compounded rubber is poured into the mold and vulcanized on a flat plate at a temperature of 175°C for 10 minutes.
[0105] The dimensions of the sample to be tested are 12.5cm*12.5cm*2mm (length*width*thickness).
[0106] The test sample was subjected to the following tests: 1. Use an insulation resistance tester to test the surface resistance RS and volume resistance RV of the silicone test piece.
[0107] 2. Use a surface voltage tester to test the static voltage.
[0108] The insulation resistance tester, model ZC-36, was purchased from Shanghai Anbiao Electronics Co., Ltd. The specific testing method is as follows: The sample to be tested is placed in the resistance testing chamber, and the resistance of the sample is tested by adjusting the voltage and current input to the instrument.
[0109] The surface voltage tester, model FMX-004, was purchased from Schleider Electric. The specific testing method is as follows: Place the test piece horizontally on the test platform and slowly bring the tester close to the test piece. When the distance to the test piece is about 25mm, the screen will display the static voltage value of the object's surface.
[0110] The experimental data are detailed in Table 1.
[0111] Table 1
[0112] Based on the data comparison of the various embodiments and comparative examples in Table 1, it can be seen that although the resistance of comparative examples 16-18 is relatively high, the surface static voltage is also relatively high, proving that the addition of a small amount of ionic liquid is difficult to reduce the surface static voltage of silicone rubber.
[0113] Examples 1-3 and Comparative Examples 1-15 have similar resistances and all exhibit high insulation performance. Furthermore, the surface voltage of Comparative Examples 1-15 is lower than that of Comparative Examples 16-18, and the surface voltage of the examples is significantly lower than that of Comparative Examples 1-15. This demonstrates that by combining ionic liquids with lignin, the surface voltage of silicone rubber can be reduced even with a low amount of ionic liquid added. However, the effect of arbitrarily combining ionic liquids and lignin in reducing the surface voltage of silicone rubber is insufficient to meet requirements; static voltages exceeding 100V can still easily affect electronic components. In contrast, when N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt, esterified lignin, and alkylated lignin are combined, the effect of reducing the surface voltage of silicone rubber is very significant, reducing the surface voltage to a safe range with almost no impact on electronic components. This effectively meets the requirements of applications requiring high insulation and sensitive to static voltage.
[0114] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A silicone rubber composition with low surface voltage, characterized in that: The components include the following parts by mass: 100 parts of methyl vinyl-terminated siloxane; 40-60 parts of silica; 0.5-0.7 parts of silane coupling agent; 4.5-5.5 parts of structure control agent; Internal release agent 0.3-0.6 parts; 0.1-0.3 parts of ionic liquid; 2-4 parts lignin; The ionic liquid is a combination of N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt and tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt; The lignin is a blend of esterified lignin and alkylated lignin.
2. The low surface voltage silicone rubber composition according to claim 1, characterized in that: In the ionic liquid, the mass ratio of N-propyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt to tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt is 0.05-0.15:0.05-0.
15.
3. The low surface voltage silicone rubber composition according to claim 2, characterized in that: The mass ratio of esterified lignin to alkylated lignin in the lignin is 1-2:1-2.
4. The low surface voltage silicone rubber composition according to claim 1, characterized in that: The structure control agent is a compound of hydroxyl silicone oil and diethoxydimethylsilane.
5. The low surface voltage silicone rubber composition according to claim 4, characterized in that: In the structure control agent, the mass ratio of hydroxyl silicone oil to diethoxydimethylsilane is 1.5-2.5:2.5-3.
6. The low surface voltage silicone rubber composition according to claim 1, characterized in that: The internal release agent is zinc stearate.
7. The low surface voltage silicone rubber composition according to claim 1, characterized in that: The silane coupling agent is a compound of vinyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.
8. The low surface voltage silicone rubber composition according to claim 7, characterized in that: In the silane coupling agent, the mass ratio of vinyltrimethoxysilane to γ-methacryloxypropyltrimethoxysilane is 0.2-0.3:0.3-0.
4.
9. A method for preparing a low surface voltage silicone rubber composition according to any one of claims 1-8, characterized in that: Includes the following steps: Step 1), mix the methyl vinyl-terminated siloxane, silane coupling agent, structure control agent, internal release agent and ionic liquid evenly to obtain a premixed adhesive; Step 2), add the silica to the premixed adhesive in 4-6 portions, and add all the lignin when adding the silica for the first time. Knead and stir evenly to obtain the mixed adhesive. Step 3), at 140-145℃, reduce the pressure to 0.05-0.08MPa, and continue kneading and stirring for 60-70 minutes to obtain the pretreated adhesive; Step 4): After cooling the pretreated adhesive to room temperature, grind the pretreated adhesive to obtain a silicone rubber composition with low surface voltage.